Investigation of temperature conditions in Swiss urban and suburban microhabitats for the overwintering suitability of diapausing Aedes albopictus eggs - Damiana Ravasi; Valeria Guidi; Eleonora Flacio; Peter Lüthy; Karl Perron; Samuel Lüdin; Mauro Tonolla (Parasites & Vectors, 2018)
Abstract Background In Switzerland, the invasive Asian tiger mosquito, Aedes albopictus, is firmly established in the Canton of Ticino, south of the Alps. According to a large-scale distribution model developed in 2013, suitable climatic conditions for the establishment of Ae. albopictus north of the Alps are found in Basel and Geneva while Zurich appears to be characterized by winters currently being too cold for survival of diapausing eggs. However, the spatial resolution of large-scale distribution models might not be sufficient to detect particular climatic conditions existing in urban settings, such as the presence of microclimatic temperatures, which may positively influence the probability of diapausing eggs to overwinter. In order to investigate this, microclimatic monitoring of potential diapausing sites (i.e. catch basins) and external controls was performed in January 2017 in Ticino and within the cities of Basel, Geneva and Zurich. Results Mean January temperatures in catch basins of Basel, Geneva and Zurich were always higher than the -1 °C temperature threshold previously set for survival probability of diapausing eggs, while mean January temperatures were below -1 °C in several catch basins south of the Alps, where Ae. albopictus eggs currently overwinter. The catch basin absolute January daily minimum temperatures both south and north of the Alps were in general higher than the external control temperatures. Absolute January daily minimum temperatures in catch basins in Basel, Geneva and Zurich were always above -10 °C, indicating that diapausing Ae. albopictus eggs could potentially survive winter nights in urban areas north of the Alps. Conclusions The findings confirmed previous conclusions that urban catch basins can provide favourable conditions for overwintering of diapausing eggs compared to more cold-exposed sites. The results confirmed the presence of suitable winter conditions for the establishment of Ae. albopictus in the cities of Basel and Geneva. In addition, the microclimate-scale analysis added new information compared to the previous large-scale prevision model by showing that also the city of Zurich could provide winter conditions suitable for the establishment of Ae. albopictus. This illustrates the importance of the resolution of climate data in using models to predict Ae. albopictus distribution.